Technological Perceptions on Human Technology Interaction (HTI) in Navigation Operation of Merchant Ships - Sakidin, S.; Chew, B.C.; Hamid, S.R.; Subramaniam, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper highlighted the perception of seafarers on Human Technology Interaction (HTI) in the navigation operation of merchant ships. From the review of the literatures, weaknesses related to HTI in the current practice of navigation were found. Most common errors found were over reliance on technology, misinterpretations of data and careless usage of technology. Due to these weaknesses, a survey titled ‘The Technological Perception on Human Technology Interaction (HTI) for Navigation of Merchant Shipping’ was conducted focusing on the perception of officers in handling the technological equipment during the navigation operation. The survey involved 97 officers of merchant ships from two major shipping companies in Asia. Among the findings were 56% officers agreed that accident happened frequently due to misinterpretation of data provided by the technological equipment. About 67% of officers agreed that logic diagrams should be provided for equipment. Recommendations were made such as to provide logic diagrams showing the relationship between the equipment and the system. A clear policy on the use of technology particularly for navigation operation should be developed especially the trend of future ships are more technologically inclined. Lastly, there is a need to explore the ergonomic compatibility for effectively eliminating the HTI errors.